The continuum of research on school permanence: Movements for resistance - da Silva, Jailson Costa; Freitas, Marinaide Lima de Queiroz (Education Policy Analysis Archives, 2022)
This paper presents research carried out at the Federal Institute of Alagoas (Ifal) that focused on the school permanence of working students of Proeja. We used the life history method as a bridge between the individual and the social, based on Cipriani (1988) and Paulilo (1999). The continuum of research across three campuses constitutes a resistance, in terms of ensuring Proeja’s courses remain based on their results and opening space for the improvement of IFAL’s existing permanence policy. Yet we conclude that IFAL needs to give more emphasis to working students in both material and symbolic aspects.